Does Surgical Menopause Affect Sexual Performance Differently from Natural Menopause?. (29th April 2015) - Kokcu, Arif; Kurtoglu, Emel; Bildircin, Devran; Celik, Handan; Kaya, Aysegul; Alper, Tayfun
Abstract Introduction Hysterectomy is the most common major gynecologic operation, together with bilateral salpingo‐oophorectomy in the majority of women over the age of 45. Aim To investigate whether surgical menopause affects female sexual performance differently from natural menopause. Methods The study included 121 women who had undergone surgical menopause and 122 women who had undergone natural menopause. All the women had similar economic, sociocultural, and personal demographic profiles, had been postmenopausal for at least 1 year, and were between the ages of 45 and 65. The women were asked to complete a six‐question survey of sexual performance parameters (sexual desire, coital frequency, arousal, orgasm frequency, dyspareunia, and vaginal lubrication). These sexual performance parameters were compared between the surgical and natural menopause groups. Results With the exception of vaginal lubrication, sexual performance parameters were not statistically different between the two groups (P > 0.05). Vaginal lubrication in the surgically menopausal group was lower than in the naturally menopausal group (P < 0.05). Serum dehydroepiandrosterone sulphate, prolactin, and thyrotropin levels were not statistically different between the groups (P > 0.05), whereas serum estradiol and total testosterone levels in the surgically menopausal group were lower than those of the naturally menopausal group (P < 0.05). Conclusion The results of this study showed that surgical menopause did not affect female sexual performance differently from natural menopause, with the exception of vaginal lubrication. Kokcu A, Kurtoglu E, Bildircin D, Celik H, Kaya A, and Alper T. Does surgical menopause affect sexual performance differently from natural menopause? J Sex Med 2015;12:1407–1414.